Towards a conceptual model for examining the impact of knowledge management factors on mobile learning acceptance - Al-Emran, Mostafa; Mezhuyev, Vitaliy; Kamaludin, Adzhar (Elsevier Ltd, 2020)
A vast amount of research has been devoted to examine the determinants influencing the acceptance of Mobile learning (M-learning). Nevertheless, little is known about studying the effect of knowledge management (KM) factors on M-learning acceptance. Therefore, the core objective of the present study is to develop a conceptual model by extending the technology acceptance model (TAM) with KM factors (acquisition, sharing, application, and protection) to examine the M-learning acceptance. This study employs the Partial Least Squares-Structural Equation Modeling (PLS-SEM) to validate the developed model. Data were gathered from 416 IT undergraduate students registered at Universiti Malaysia Pahang (UMP) in Malaysia. The results triggered out that knowledge acquisition, application, and protection have positive impacts on perceived ease of use and perceived usefulness. However, knowledge sharing was observed to be partially supported with regard to perceived ease of use and perceived usefulness. The implications to theory and practice, limitations, and future work are also discussed.